Determinants Of The Quality Of Audit Services Moderated By The Auditor's Professional Ethics In The Public Accounting Office Of The South Jakarta Region - Anisa Trisnowati, Dian; Apollo, Apollo (Green Publisher Indonesia, 2022)
The COVID-19 pandemic affected audit quality due to various policies implemented by the government itself to deal with the pandemic, such as social distancing, work from home and even lockdowns which made it difficult for auditors to verify the findings they obtained during the audit. auditors who cannot perform audit procedures in accordance with applicable auditing standards, the auditors cannot issue quality audit reports and provide opinions that are not in accordance with the audit standard code of ethics, meaning that they do not apply professional audit ethics so that the auditor does not have the competence, professionalism and may not have the ability to manage information technology. This research is a quantitative research with primary data. The data collection technique used a questionnaire that was distributed to respondents to auditors working at KAP with active status in the South Jakarta area, with a total sample of 97 auditors. The results showed that the application of information technology, competence, and professionalism had a significant effect on the quality of audit services. As well as professional ethics of auditors is able to strengthen the relationship between the application of information technology, competence, and professionalism to the quality of audit services